Effects of solvent and structure on the reactivity of 6-substituted nicotinic acids with diazodiphenylmethane in aprotic solvents - Drmanić Saša Ž.; Marinković Aleksandar D.; Jovanović Bratislav Ž. (Journal of the Serbian Chemical Society, 2009)
The rate constants for the reactions of diazodiphenylmethane (DDM) with 6-substituted nicotinic acids in aprotic solvents at 30°C were determined. The obtained second order rate constants in aprotic solvents, together with literature data for benzoic and nicotinic acids in protic solvents, were used for the calculation of solvent effects, employing the Kamlet-Taft solvatochromic equation (linear solvation energy relationship - LSER) in the form: log k = log k0 + + sΠ*+ aα + bβ. The correlations of the kinetic data were performed by means of multiple linear regression analysis taking appropriate solvent parameters. The sign of the equation coefficients (s, a and b) were in agreement with the postulated reaction mechanism, and the mode of the solvent influences on the reaction rate is discussed based on the correlation results. A similar contribution of the non-specific solvent effect and electrophilic solvation was observed for all acids, while the highest contribution of nucleophilic solvation was influenced by their high acidity. Correlation analysis of the rate data with substituent óp parameters in an appropriate solvent using the Hammett equation was also performed. The substituent effect on the acid reactivity was higher in aprotic solvents of higher dipolarity/polarizability. The mode of the transmission of the substituent effect is discussed in light of the contribution of solute-solvent interaction on the acid reactivity.